2007
DOI: 10.1021/ma062821f
|View full text |Cite
|
Sign up to set email alerts
|

pH-Responsive Thin Film Membranes from Poly(2-vinylpyridine):  Water Vapor-Induced Formation of a Microporous Structure

Abstract: We report the fabrication of microporous thin film membranes with two-dimensionally arranged submicron pores whose size can be varied by changing pH of aqueous medium. A solution containing poly(2-vinylpyridine) partially quaternized with 1,4-diiodobutane (qP2VP) and unreacted 1,4-diodobutane (DIB) was used for the formation and deposition of the membranes on solid substrates. The membranes were spin-coated onto solid substrates in a controlled humid environment. The presence of water vapor in air was found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
57
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 42 publications
(63 reference statements)
0
57
0
Order By: Relevance
“…[1][2][3] Coaxial electrospinning, comparing to simple single and blended spinning, is used to prepare core-sheath structured nanofibers with outstanding properties and multifunctionality for additional functional applications, [4][5] such as biotechnology, textiles, membranes, composites. [6][7][8][9] Stimuli-responsive polymers have been widely used in intelligent or smart materials with a great promise in drug delivery systems, sensors, and biomaterials, [10][11][12][13][14][15] due to these polymers can respond to changes in temperature, pH, light, or ionic strength. For example, poly(N-isopropylacrylamide) (PNIPAAm) is a typical temperature-sensitive polymer.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Coaxial electrospinning, comparing to simple single and blended spinning, is used to prepare core-sheath structured nanofibers with outstanding properties and multifunctionality for additional functional applications, [4][5] such as biotechnology, textiles, membranes, composites. [6][7][8][9] Stimuli-responsive polymers have been widely used in intelligent or smart materials with a great promise in drug delivery systems, sensors, and biomaterials, [10][11][12][13][14][15] due to these polymers can respond to changes in temperature, pH, light, or ionic strength. For example, poly(N-isopropylacrylamide) (PNIPAAm) is a typical temperature-sensitive polymer.…”
Section: Introductionmentioning
confidence: 99%
“…These membranes were cross-linked by temperature annealing and after cross-linking membranes demonstrated pH-dependent swelling, which makes them potentially attractive for size dependent filtering, drug delivery systems, and sensors. 227 Munoz Bonilla et al obtained breath figure patterns on functional surfaces by the surface segregation of a statistical glycopolymer, (S-co-2-(D-glucopyranosyl) aminocarbonyloxy ethyl acrylate. The blends of this copolymer and high-molecular-weight PS were spin coated from THF solutions and it was shown that blend composition and relative humidity play an important role in the size and distribution of the pores.…”
mentioning
confidence: 99%
“…[42,43] The cross-linked P2VP gel film grafted onto a silicon wafer with a native oxide layer of $1 nm shows uniform and smooth surface morphology (see Fig. S1, Supporting Information (SI)).…”
mentioning
confidence: 99%